Pathological changes induced by BaH1, a hemorrhagic proteinase isolated from Bothrops asper (Terciopelo) snake venom, on mouse capillary blood vessels - Moreira Carmona, Lisela (1994)
The pathological changes induced in capillaries by BaH1, a hemorrhagic metalloproteinase isolated from the venom of Bothrops asper, were studied after i.m. injection in mouse gastrocnemius. Hemorrhage was observed macroscopically, and corroborated histologically, within the first 5 min. At the ultrastructural level, the earliest changes in endothelial cells, observed 1 min after toxin administration, consisted of a decrease in the number of pinocytotic vesicles, the presence of blebs and cytoplasmic projections pinching off to the vascular lumen and the detachment of endothelial cells from the surrounding basal lamina. These processes occurred concomitantly with a thinning of endothelial cells. In capillaries undergoing more advanced degenerative stages, there were gaps or breaks in endothelial cells through which erythrocytes were escaping to the extravascular space. In these cells, the basal lamina was usually absent. Throughout this process, intercellular junctions remained apparently intact and no evidence was found of extravasation through widened intercellular junctions. In addition to this morphological pattern of degeneration, some capillaries presented swollen endothelial cells with dilated endoplasmic reticulum and lacking pinocytotic vesicles. Many capillaries contained platelet plugs and fibrin. Thus, hemorrhage induced by BaH1 occurs per rhexis, as has been also described for other venoms and hemorrhagic toxins.